First steps into the world of systolic inequalities: from riemannian to symplectic geometry - Benedetti, Gabriele (Arxiv, 2021)
Our aim is to give a friendly introduction for students to systolic inequalities. We will stress the relationships between the classical formulation for Riemannian metrics and more recent developments related to symplectic measurements and the Viterbo conjecture. This will give us a perfect excuse to introduce the reader to some important ideas in Riemannian and symplectic geometry.
Artikelversion vom 25. August 2021
Gesehen am 09.01.2024